2017
DOI: 10.1007/s00216-017-0238-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the specific interaction between the DNA aptamer sgc8c and protein tyrosine kinase-7 receptors at the surface of T-cells by biosensing AFM

Abstract: We studied the interaction of the specific DNA aptamer sgc8c immobilized at the AFM tip with its corresponding receptor, the protein tyrosine kinase-7 (PTK7) embedded in the membrane of acute lymphoblastic leukemia (ALL) cells (Jurkat T-cells). Performing single molecule force spectroscopy (SMFS) experiments, we showed that the aptamer sgc8c bound with high probability (38.3 ± 7.48%) and high specificity to PTK7, as demonstrated by receptor blocking experiments and through comparison with the binding behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 62 publications
2
14
0
Order By: Relevance
“…Our experiments showed that the binding probability was highest for MOLT‐4 cells (48.6±3.9 %) and lowest for U266 cells (3.3±1.5). The binding probability for Jurkat cells were 37.5±5.0 % and this is in good agreement with work by Leitner at al . Figure SI‐3 in Supporting information summarizes all experiments on the cells including U266 cells that do not contain PTK7 receptors.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Our experiments showed that the binding probability was highest for MOLT‐4 cells (48.6±3.9 %) and lowest for U266 cells (3.3±1.5). The binding probability for Jurkat cells were 37.5±5.0 % and this is in good agreement with work by Leitner at al . Figure SI‐3 in Supporting information summarizes all experiments on the cells including U266 cells that do not contain PTK7 receptors.…”
Section: Resultssupporting
confidence: 88%
“…The principle of this measurement is based on the direct relation between voltage of photodiode and the bending of the cantilever, which can be considered as a spring. Using the Hooke's law it is possible to transform this bending into the force . For each AFM tip we have measured 5 retraction velocities in the range from 300 to 7500 nm/s.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, rapid, selective and specific methods are urgently in demand. Based on the specific interaction of DNA Sgc8c aptamer and PTK-7 on ALL cells,85 a growing number of sophisticated diagnostic methods have been created. In one report, biotin-modified semiconductor QDs were labeled with the Sgc8 aptamer via streptavidin, then a stronger fluorescent signal would be generated by biotin amplification interactions when Sgc8 aptamer identified CCRF-CEM cells in T-ALL,67 In another report, dual-aptamer (Sgc8c and ATP aptamers)-functionalized graphene oxide (DAFGO) complex, consisting of bispecific aptamers (Sgc8c and ATP aptamers) and graphene oxide (GO), was designed for internalization into Molt-4 T-ALL cells,86 Sgc8c aptamer was selected and characterized to target to PTK-7.…”
Section: Aptamers As Diagnostic Tools In Leukemiamentioning
confidence: 99%